Identification of 15- to 17-kilodalton antigens associated with virulent Rhodococcus equi. - Takai, S (1991)
Antigens of Rhodococcus equi were analyzed by immunoblotting with naturally infected foal sera. Immunoblots of whole-cell antigen preparations of clinical isolates of R. equi revealed that major protein bands with molecular masses of 15 to 17 kDa were present in all clinical isolates tested and all isolates virulent for mice. In contrast, the 15- to 17-kDa antigens were not identified by immunoblotting in ATCC 6939, a type strain of R. equi that was avirulent for mice. Whole-cell antigens of 102 environmental isolates were investigated by immunoblotting and the mouse pathogenicity test. Twenty-five of these isolates were demonstrated to contain the 15- to 17-kDa antigens by immunoblotting and were virulent for mice. The remaining 77 environmental isolates lacked the 15- to 17-kDa antigens and were avirulent for mice. These data suggest that the diffuse 15- to 17-kDa proteins are virulence-associated antigens with immunogenicity in foals and that they may be useful in marking virulent R. equi contamination in the environment of a horse-breeding farm.